Design and Development of the Boarding House Management Information System (SIMKO) Using Laravel with Agile Methodology - Mirza Khazim Nugraha; Nur Cahyo Wibowo; Iqbal Ramadhani Mukhlis (Universitas Islam Kuantan Singingi, 2025)
The manual management of boarding houses often causes various problems, such as inaccurate recording of transactions and tenant data, lack of information for prospective tenants, and unstructured booking and payment processes. This research aims to design and build a web-based Boarding House Management Information System (SIMKO) using the Laravel framework and the Agile development method. Data is collected through literature studies, interviews with boarding house owners, and direct observation of boarding houses in the Sedati area. The result of this research is an integrated information system with main features such as boarding house search, filing complaints, recording tenant and transaction data, booking rooms, financial reports, and digital payment support through Xendit. The development process is iterative and flexible to adjust to user needs. This system is expected to increase transparency, as well as the overall quality of boarding business management services.